Enantiomeric alkynyl-protected Au10 clusters with chirality-dependent radiotherapy enhancing effects. (August 2021) - Jia, Tong-Tong; Li, Bing-Jie; Yang, Guang; Hua, Yue; Liu, Jun-Qi; Ma, Wang; Zang, Shuang-Quan; Chen, Xiaoyuan; Zhao, Xueli
Highlights: Stereospecific interactions between chiral AuNCs and proteins resulted different size distributions of L/D-NCs in cell medium. D-AuNCs exhibited lower cytotoxicity compared with L-AuNCs. The radiosensitizating efficiency of D-AuNC was higher than L-AuNC. Chirality of metal clusters has significant effect on radiotherapy. Graphical Abstract: ga1 Abstract: Due to the homo-chirality preference of human body to most of chiral species, synthesizing enantiopure drugs and investigating the pharmacological activity of each enantiomer would have great meaning. However, the influence of chirality at nanoscale on the ability to enhance radiotherapy has not been studied. Herein, a pair of enantiomeric alkynyl-protected L/D-Au10 (C13 H17 O5 )10 nanoclusters (L/D-AuNCs) with strong chirality (g value up to 3.6 × 10 -3 ) and circular polarization luminescence (glum ≈ 3 × 10 -3 ) are prepared and applied as radiosensitizers. As a consequence, D-AuNCs exhibit better radiosensitization effect in vitro, which is confirmed by research on mechanisms including reactive oxygen species (ROS) burst mediated DNA breakage, cell cycle arrest and up-regulation of apoptotic protein expression. In vivo antitumor studies manifest that tumors treated with D-AuNCs and X-ray show a volume decrease of 51% compared with X-ray (4 Gy) only group. This work not only enriches the family of gold-based nano-radiosensitizers, but also further proves the significance of chirality in biomedicine.